Superconductor-metal conductive material and electronic component and forming method thereof
By using superconductor-metal conductive materials in passive components, the problems of poor current input and mismatch of material expansion coefficient in the prior art under ultra-low temperature environment are solved, and the resistance value is reduced and the reliability and energy efficiency of the component are improved.
Patent Information
- Application Number
- CN202411118563.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-16
- Filing Date
- 2024-08-15
- Publication Date
- 2025-02-21
AI Technical Summary
The existing passive components frequently fail in ultra-low temperature environments below 223K, mainly due to poor current input and mismatch in the expansion coefficients of the ceramic layer and the conductor layer, resulting in structural damage and electrical failure.
Using superconductor-metal conductive material, by mixing superconducting oxide powder with metal powder and organic carrier adhesive, the conductive material is formed, and the material is coated on the ceramic layer to form a conductive layer, using the expansion of superconducting oxide The coefficient adjusts the expansion coefficient of the metal composite slurry to match it with the ceramic material.
It significantly reduces the resistance value of electronic components in low temperature environments, improves component reliability and energy efficiency, reduces the chance of failure, and maintains good performance in high temperature environments.
Smart Images

Figure CN119495471A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of resistor materials, and in particular relates to a conductive oxide-metal conductive material and a preparation method thereof. Background Art
[0002] With the development of modern electronic industry, information industry and high-tech, the demand for conductive composite materials is increasing, and conductive composite materials are receiving more and more attention. The research on conductive composite materials mainly focuses on conductive polymer composite materials, while the research on using superconductor powder as conductive filler is relatively small. As the use environment of electronic components is more demanding, special selection and design of internal or external conductive materials are required.
[0003] Among existing passive components (MLCC, varistors, thermistors, chip inductors), failures in ultra-low temperature environments below 223K are mostly due to the inability to effectively input current into the components. In addition, the mismatch in expansion coefficients can cause discontinuity between the conductor layer and the ceramic layer, leading to structural damage and electrical failure of the components. Therefore, there is an urgent need to develop passive components that can be used at specific ultra-low temperatures.
[0004] Therefore, the present invention proposes a new solution to overcome the above disadvantages. Summary of the invention
[0005] A first object of the present invention is to provide a superconductor-metal conductive material.
[0006] The second object of the present invention is to provide a method for preparing the above-mentioned superconductor-metal conductive material.
[0007] A third object of the present invention is to provide an electronic component comprising the above-mentioned superconductor-metal conductive material.
[0008] The present invention has the advantage of improving the reliability of passive component products in harsh low-temperature environments. In addition, by replacing glass powder with superconducting oxide, the expansion coefficient of the metal composite slurry formed by the metal conductor is adjusted by using the expansion coefficient of the superconducting oxide, so that matching with the ceramic material can be achieved. This not only reduces the impedance of the metal composite slurry, but also improves the reliability at low and high temperatures.
[0009] In one embodiment, the present invention provides a superconductor-metal conductive material, wherein a superconductor-metal conductive material comprises a metal powder, a superconductor powder and an organic carrier adhesive, wherein the metal powder accounts for 50-95wt% of the total weight of the metal powder, the superconductor powder and the organic carrier adhesive, the superconductor powder accounts for 4-40wt% of the total weight, and the organic carrier adhesive accounts for 1-10wt% of the total weight, wherein the superconductor powder comprises one or more mixtures of La2-x-ySrxBayCuO4, La2-x-yBixSryCuO4, La2-xy-zBixSryCaZCuO4, La2-xy-zHgxBayCazCuO4, La2-x-ySrxTlyBazCuO6, La2-xyz-wSrxTlyBazCawCu2O8, HgBa2Ca2Cu3O8, wherein x, y, z and w are all between 0.1 and 0.9.
[0010] In one embodiment, the average particle size of the superconductor powder is 30 nm to 300 nm.
[0011] In one embodiment, the metal powder includes one or more mixtures of Au, Ag, Cu, Sn, Ag / Pd, Pd, Al, Nb, Ti and Ni.
[0012] In one embodiment, the metal powder has an average particle size of 30 nm to 2 μm.
[0013] In one embodiment, the metal powder particles with a particle size smaller than 100 nanometers account for 10-20% of all metal powder particles, and the metal powder particles with a particle size between 100 nm and 2 μm account for 80-90% of all metal powder particles.
[0014] In one embodiment, the organic carrier binder includes a mixture of one or more of polyvinyl butyral, ethyl cellulose, polyvinyl acetate, polyethylene oxide, carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, and polymethyl methacrylate.
[0015] In one embodiment, the superconductor-metal conductive material further includes an organic solvent, and the organic solvent is a mixture of one or more of toluene, alcohol, butyl acetate, ethylene glycol monobutyl ether, and diethylene glycol.
[0016] In one embodiment, the superconductor-metal conductive material further includes a dispersant, and the dispersant includes a mixture of one or more of carboxylic acids, long-chain alkyl amino acids, polyacrylic acids, and polymethyl methacrylates.
[0017] In one embodiment, the present invention further provides an electronic component, comprising: a plurality of stacked composite layers, wherein each composite layer comprises a ceramic layer and a conductive layer made of a superconductor-metal conductive material coated on the ceramic layer, wherein the superconductor-metal conductive material comprises a metal powder, a superconductor powder and an organic carrier adhesive, wherein the metal powder accounts for 50-95wt% of the total weight of the metal powder, the superconductor powder and the organic carrier adhesive, the superconductor powder accounts for 4-40wt% of the total weight, and the organic carrier adhesive The agent accounts for 1 to 10 wt% of the total weight, wherein the superconductor powder includes one or more mixtures of La2-x-ySrxBayCuO4, La2-x-yBixSryCuO4, La2-xy-zBixSryCaZCuO4, La2-xy-zHgxBayCazCuO4, La2-x-ySrxTlyBazCuO6, La2-xyz-wSrxTlyBazCawCu2O8, and HgBa2Ca2Cu3O8, wherein x, y, z and w are all between 0.1 and 0.9.
[0018] In one embodiment, the average particle size of the superconductor powder is 30 nm to 300 nm.
[0019] In one embodiment, the metal powder includes one or more mixtures of Au, Ag, Cu, Sn, Ag / Pd, Pd, Al, Nb, Ti and Ni.
[0020] In one embodiment, the average particle size of the metal powder is 30 nm to 2 μm.
[0021] In one embodiment, the metal powder particles with a particle size smaller than 100 nanometers account for 10-20% of all metal powder particles, and the metal powder particles with a particle size between 100 nm and 2 μm account for 80-90% of all metal powder particles.
[0022] In one embodiment, the electronic component is a resistor.
[0023] In one embodiment, the electronic component is a varistor.
[0024] In one embodiment, the present invention further provides a method for forming an electronic component, comprising: coating a superconductor-metal conductive material on a ceramic layer to form a composite layer; stacking a plurality of the composite layers together, and sintering the stacked composite layers at a temperature above 800° C., wherein the superconductor-metal conductive material comprises a metal powder, a superconductor powder and an organic carrier binder, wherein the metal powder accounts for 50 to 95 wt % of the total weight of the metal powder, the superconductor powder and the organic carrier binder, and the superconductor powder accounts for 4 to 40 wt % of the total weight. %, the organic carrier binder accounts for 1 to 10 wt% of the total weight, wherein the superconductor powder includes one or more mixtures of La2-x-ySrxBayCuO4, La2-x-yBixSryCuO4, La2-xy-zBixSryCaZCuO4, La2-xy-zHgxBayCazCuO4, La2-x-ySrxTlyBazCuO6, La2-xyz-wSrxTlyBazCawCu2O8, HgBa2Ca2Cu3O8, wherein x, y, z and w are all between 0.1 and 0.9.
[0025] In one embodiment, the superconductor-metal conductive material is formed by the following steps: mixing 50-95 weight percent of metal powder with 4-40 weight percent of superconductor powder; adding 1-10 weight percent of an organic carrier binder to the mixed powder; and adding the mixture to a solvent containing a dispersant to form the superconductor-metal conductive material.
[0026] In order to enable those skilled in the art to better understand the features of the claimed invention, the detailed techniques implemented by the present invention and the above-mentioned preferred embodiments will be described in the following paragraphs in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 A schematic diagram showing a plurality of ceramic layers and a conductive layer according to an embodiment of the present invention is shown;
[0028] Figure 2 A schematic diagram showing an electronic component according to an embodiment of the present invention is shown;
[0029] Figure 3 A schematic diagram showing an electronic component according to an embodiment of the present invention is shown;
[0030] Figure 4 shows a 3D view of an electronic component according to one embodiment of the present invention; and
[0031] Figure 5 A 3D view of an electronic component according to one embodiment of the present invention is shown.
[0032] Explanation of the figure marks: 101CL-first composite layer; 101a-first ceramic layer; 101b-first conductive layer; 102CL-second composite layer; 102a-second ceramic layer; 102b-second conductive layer; 103a-third ceramic layer; T1, T2-terminals; 101CS-multiple ceramic layers; 102ES-multiple conductive layers; 101CB-ceramic body; T1a-innermost layer of the terminal; T1b-middle layer of the terminal; T1c-outermost layer of the terminal. DETAILED DESCRIPTION
[0033] The present invention provides a superconductor-metal conductive material, wherein the superconductor-metal conductive material comprises a metal powder, a superconductor powder and an organic carrier adhesive, wherein the metal powder accounts for 50-95wt% of the total weight of the metal powder, the superconductor powder and the organic carrier adhesive, the superconductor powder accounts for 4-40wt% of the total weight, and the organic carrier adhesive accounts for 1-10wt% of the total weight, wherein the superconductor powder comprises one or more mixtures of La2-x-ySrxBayCuO4, La2-x-yBixSryCuO4, La2-xy-zBixSryCaZCuO4, La2-xy-zHgxBayCazCuO4, La2-x-ySrxTlyBazCuO6, La2-xyz-wSrxTlyBazCawCu2O8, HgBa2Ca2Cu3O8, wherein x, y, z and w are all between 0.1 and 0.9.
[0034] In one embodiment, the average particle size of the superconductor powder is 30 nm to 300 nm.
[0035] In one embodiment, the metal powder includes one or more mixtures of Au, Ag, Cu, Sn, Ag / Pd, Pd, Al, Nb, Ti, and Ni.
[0036] In one embodiment, the average particle size of the metal powder is 30 nm to 2 μm.
[0037] In one embodiment, 10-20% of the metal powder has a particle size <100 nm, and 80-90% of the remaining metal powder has a particle size between 100 nm and 2 μm.
[0038] In one embodiment, the organic vehicle binder includes a mixture of one or more of polyvinyl butyral, ethyl cellulose, polyvinyl acetate, polyethylene oxide, carboxymethyl cellulose, styrene butadiene rubber, polyacrylic acid, and polymethyl methacrylate.
[0039] In one embodiment, the superconductor-metal conductive material further includes a solvent, and the solvent includes an organic solvent or an aqueous solvent, and the organic solvent is a mixture of one or more of toluene, alcohol, butyl acetate, ethylene glycol monobutyl ether, and diethylene glycol monobutyl ether.
[0040] In one embodiment, the superconductor-metal conductive material further includes a dispersant, and the dispersant includes a mixture of one or more of carboxylic acids, long-chain alkyl amino acids, polyacrylic acids, and polymethyl methacrylates.
[0041] Figure 1 A structural diagram of an electronic component having a plurality of ceramic layers and a conductive layer according to an embodiment of the present invention is shown. Figure 2 A schematic diagram of an electronic component of an embodiment of the present invention is shown, wherein the electronic component includes a plurality of composite layers 101CL and 102CL stacked together, wherein the first composite layer 101CL includes a first ceramic layer 101a and a first conductive layer 101b made of a superconducting-metal conductive material coated on the first ceramic layer 101a, and the second composite layer 102CL includes a second ceramic layer 102a and a second conductive layer 102b made of a superconducting-metal conductive material coated on the second ceramic layer 102a, wherein the superconducting-metal conductive material includes metal powder, superconductor powder and organic carrier adhesive, wherein the metal powder accounts for 50-95wt% of the total weight of the metal powder, the superconductor powder and the organic carrier adhesive, the superconductor powder accounts for 4-40wt% of the total weight, and the organic carrier adhesive accounts for 1-10wt% of the total weight.
[0042] In one embodiment, the superconductor powder includes one or more mixtures of La2-x-ySrxBayCuO4, La2-x-yBixSryCuO4, La2-xy-zBixSryCaZCuO4, La2-xy-zHgxBayCazCuO4, La2-x-ySrxTlyBazCuO6, La2-xyz-wSrxTlyBazCawCu2O8, and HgBa2Ca2Cu3O8, wherein the value of each x, y, z and w is between 0.1 and 0.9.
[0043] In one embodiment, the electronic component is a resistor having two terminals T1 , T2 .
[0044] In one embodiment, the first conductive layer 101b includes a plurality of conductive patterns.
[0045] In one embodiment, the second conductive layer 102b includes a plurality of conductive patterns.
[0046] Figure 3 Schematic diagram of electronic components is shown. In one embodiment of the present invention, Figure 1 A third ceramic layer 103a is disposed on the second conductive layer 102b of the electronic component in the embodiment. In one embodiment, the electronic component is a resistor having two terminals T1, T2.
[0047] Figure 4 A schematic 3D view of an electronic component is shown. In one embodiment of the present invention, the electronic component comprises a plurality of ceramic layers 101CS and a plurality of conductive layers 102ES, wherein the corresponding ceramic layers are coated with conductive layers made of superconducting-metallic conductive material. In one embodiment, the electronic component is a resistor having two terminals T1, T2.
[0048] Figure 5 A schematic 3D view of an electronic component is shown, in an embodiment of the present invention, wherein the electronic component comprises a ceramic body 101CB having a plurality of ceramic layers 101CS, wherein a plurality of conductive layers 102ES are arranged in the ceramic body 101CB, wherein the conductive layers are made of a superconductor metal conductive material coated on the respective ceramic layers. In one embodiment, the electronic component is a resistor having two terminals T1, T2.
[0049] In one embodiment, the terminal T1 has three layers, wherein the innermost layer T1a of the terminal T1 is made of Ag, the middle layer T1b of the terminal T1 is made of Ni, and the outermost layer T1c of the terminal T1 is made of Sn.
[0050] In one embodiment, the terminal T2 has three layers, wherein the innermost layer of the terminal T2 is made of Ag, the middle layer of the terminal T2 is made of Ni, and the outermost layer of the terminal T2 is made of Sn.
[0051] In one embodiment, the present invention provides an electronic component, comprising: a plurality of composite layers stacked together, wherein each composite layer comprises a dielectric layer and a conductive layer made of a superconductor-metal conductive material coated on the dielectric layer, wherein the superconductor-metal conductive material comprises metal powder, superconductor powder and an organic carrier adhesive, wherein the metal powder accounts for 50-95wt% of the total weight of the metal powder, superconductor powder and organic carrier adhesive, the powder accounts for 4-40wt% of the total weight, and the organic carrier adhesive accounts for 1-10wt% of the total weight.
[0052] In one embodiment, the superconductor powder contains one or more mixtures of La2-x-ySrxBayCuO4, La2-x-yBixSryCuO4, La2-xy-zBixSryCaZCuO4, La2-xy-zHgxBayCazCuO4, La2-x-ySrxTlyBazCuO6, La2-xyz-wSrxTlyBazCawCu2O8, HgBa2Ca2Cu3O8, wherein the value of each x, y, z and w is between 0.1 and 0.9.
[0053] In one embodiment, the average particle size of the superconductor powder is 30 nm to 300 nm.
[0054] In one embodiment, the metal powder includes one or more mixtures of Au, Ag, Cu, Sn, Ag / Pd, Pd, Al, Nb, Ti, and Ni.
[0055] In one embodiment, the average particle size of the metal powder is 30 nm to 2 μm.
[0056] In one embodiment, 10-20% of the metal powder has a particle size <100 nm, and 80-90% of the remaining metal powder has a particle size between 100 nm and 2 μm.
[0057] In one embodiment, the electronic component is a resistor.
[0058] In one embodiment, the electronic component is a varistor.
[0059] In one embodiment, the present invention provides a method for forming a ceramic electronic component, comprising: coating a superconductor-metal conductive material on a ceramic layer to form a composite layer; stacking a plurality of composite layers together, and sintering the stacked plurality of composite layers at a temperature above 800° C. to obtain a ceramic electronic component.
[0060] In one embodiment, the superconductor-metal conductive material comprises metal powder, superconductor powder and organic carrier binder, wherein the metal powder accounts for 50-95wt% of the total weight of the metal powder, superconductor powder and organic carrier, and the binder, the superconductor powder accounts for 4-40wt% of the total weight, and the organic carrier binder accounts for 1-10wt% of the total weight.
[0061] In one embodiment, the superconducting powder comprises one or a mixture of more of La2-x-ySrxBayCuO4, La2-x-yBixSryCuO4, La2-x-y-zBixSryCaZCuO4, La2-x-y-zHgxBayCazCuO4, La2-x-ySrxTlyBazCuO6, La2-x-y-z-wSrxTlyBazCawCu2O8, HgBa2Ca2Cu3O8, wherein the value of each of x, y, z, and w is between 0.1 and 0.9.
[0062] In one embodiment, the superconductor-metal conductive material is formed by the following steps: mixing 50-95 weight percent of metal powder with 4-40 weight percent of superconducting powder. Adding 1-10 weight % of an organic carrier binder to the mixed powder; adding the mixture to a solvent containing a dispersant to obtain the superconductor-metal conductive material.
[0063] Example 1: Preparation of a conductive paste. The steps for forming the superconductor-metal conductive material are as follows: Step 1: Silver powder processing: The average particle size of the processed silver powder is 50 nm to 5 μm. Among them, the particles less than 100 nm account for 30%, and the remaining particles between 100 nm and 5 μm account for 70%; Step 2: Processing the superconductor La2-x-ySrxTlyBazCuO6: The average particle size of the processed superconducting powder is between 30 nm and 500 nm; Step 3: Mixing: Take 80 wt% of Ag powder and 20 wt% of La2-x-ySrxTlyBazCuO6, and mix the superconducting powder evenly, wherein the range of variables is: 0.2 < x < 0.8, 0.3 < y < 0.7, and 0.2 < z < 0.6; Step 4: Mix the superconducting powder evenly; Step 5: Add a binder: Add 5-10 weight % (relative to the solid metal and superconducting powder) of the binder polyvinyl butyral (PVB); add a mixed solvent of alcohol and butyl acetate containing 1-10 wt% of the BYK110 dispersant; stir and mix evenly to obtain a conductive paste; Step 6: Coating and sintering: Attach the conductive paste to the ceramic body by a certain method to form a dielectric layer; and sinter at a temperature above 850 °C for 2 hours.
[0064] Usage method: Use the obtained ceramic electronic component in a liquid nitrogen low-temperature environment (77K to 223K). The superconducting powder helps the conduction path and reduces the resistance value to 1×10 -4 Ω·cm. In addition, the energy consumption of the component is reduced by about 30%.
[0065] Example 2: Preparation of conductive paste: A superconductor-metal conductive material is formed by the following steps: Step 1: Treating palladium (Pd): The average particle size of the treated Pd powder is 50 nm to 3 μm. Among them, particles smaller than 100nm account for 20%, and the remaining particles between 100nm and 3μm account for 80%; Step 2: Processing of superconductor Bi2Sr2CaCu2O8: The average particle size of the processed superconductor powder is between 50nm and 300nm; Step 3: Mixing: Take 80wt% of Ag powder, 10wt% of HgBa2Ca2Cu3O8 superconductor powder, and 10wt% of Bi2Sr2CaCu2O8 superconductor powder; Mix the powders evenly; Step 4: Add binder: Add 5-10wt% (relative to solid metal and superconductor powder) of binder ethyl cellulose, add butyl acetate and ethylene glycol monobutyl ether mixed solvent containing 1-10wt% BYK163 dispersant, stir and mix evenly to obtain a conductive slurry; Step 5: Coating and sintering: The conductive slurry is attached to the ceramic body by a certain method to form a dielectric layer, and sintered at a temperature above 950°C for 2 hours.
[0066] Usage: The obtained ceramic electronic components are used in a liquid nitrogen cryogenic environment (77K to 223K). The superconductor powder helps the conductive path and reduces the resistance value to 1×10 -4 Ω·cm. In addition, the energy consumption of the component was reduced by about 35%.
[0067] Example 3: Preparation of conductive paste: The superconductor-metal conductive material is formed by the following steps: Step 1: Ag / Ti processing: The average particle size of the processed Ag / Ti powder is 50nm to 3μm. Among them, particles smaller than 100nm account for 20%, and the remaining particles between 100nm and 3μm account for 80%; Step 2: Processing superconductor Tl2Ba2CaCu2O8: The average particle size of the processed superconductor powder is between 50nm and 300nm. Step 3: Mixing: Take 80wt% Ag / Ti powder, 10wt% HgBa2Ca2Cu3O8 superconductor powder, and 10wt% Tl2Ba2CaCu2O8 superconductor powder, and mix them evenly; Step 4: Adding binder: Add 5-10wt% (relative to solid metal and superconductor powder) of binder ethyl cellulose, add a mixed solvent of diethylene glycol monobutyl ether and pine alcohol containing 1-10wt% BYK110 dispersant, stir and mix evenly to obtain a conductive slurry; Step 5: Coating and sintering: Use a certain method to attach the conductive slurry to the ceramic body to form a dielectric layer. Sinter at a temperature above 850°C for 2 hours.
[0068] Usage: The obtained ceramic electronic components are used in a liquid nitrogen cryogenic environment (77K to 223K). The superconductor powder helps the conductive path and reduces the resistance value to 1×10-4 Ω·cm. In addition, the energy consumption of the component was reduced by about 30%.
[0069] The measurement method of resistance value is as follows: square resistance, where square resistance refers to the resistance from edge to edge of the square sample to be measured, which is only related to the resistivity and thickness of the sample. The calculation formula is: R = ρ / d, ρ is the resistivity of the material, and d is the thickness of the sample. The four-probe method is usually used for measurement. The relationship is R = V / I·F(D / S)·F(W / S)·Fsp, where I is the current value flowing through the two probes at the outer end, V is the value between the inner end, and F(D / S), F(W / S) and Fsp are the correction factors of the instrument. During the test, a certain current is applied between the probes at the two ends of the instrument, and the square resistance value of the material is obtained by obtaining the potential difference between the two probes at the inner end.
[0070] Manufacturing method: Preparation of conductive slurry: Process metal into powder: convert metal into powder form, process superconductor into powder: convert superconductor into powder form; Mix: Take 80 weight% of metal powder and 20 weight% of superconductor powder, mix evenly; Add binder and dispersant: Add 5-10 weight% (relative to solid metal and superconductor powder) of binder and stir evenly; Add dispersant, stir and mix evenly to obtain conductive slurry; Coating and sintering: Attach the conductive slurry to the ceramic body to form a dielectric layer, and sinter at a temperature above 800°C for 30 minutes.
[0071] Usage: The obtained ceramic electronic components are used in a liquid nitrogen cooling environment (77K to 223K). The superconductor powder enhances the conductive path and reduces the resistance value to 1×10 -4 Ω·cm. In addition, the energy consumption of the component was reduced by about 30%.
[0072] The measurement method of resistance value is as follows: square resistance, where square resistance refers to the edge-to-edge resistance of the square sample to be measured, which is only related to the resistivity and thickness of the sample. The calculation formula is: R = ρ / d, ρ is the resistivity of the material, and d is the thickness of the sample. The four-probe method is usually used for measurement. The relationship is R = V / I·F(D / S)·F(W / S)·Fsp, where I is the current value flowing through the two probes at the outer end, V is the inner end, and F(D / S), F(W / S) and Fsp between the voltage probes are the correction coefficients of the instrument. During the test, a certain current is applied between the probes at both ends of the instrument, and the square resistance value of the material is obtained by obtaining the potential difference between the two probes at the inner end.
[0073] The present invention provides a method for preparing a ceramic electronic component with a superconductor-metal conductive material, and the steps are as follows: Step 01: coating a superconductor-metal conductive material on a ceramic layer to form a dielectric / ceramic composite layer. Step 02: stacking a plurality of ceramic bodies with dielectric layers together and sintering them at a temperature above 800°C to obtain a multilayer ceramic electronic component.
[0074] The present invention provides a method for preparing a superconductor-metal conductive material, and the steps are as follows: Step 01: Mix 50-95 weight percent of metal powder and 4-40 weight percent of superconductor powder. Step 02: Add 1-10 weight percent of an organic carrier binder to the mixed powder; Step 03: Add the mixture to a solvent containing a dispersant, mix and stir evenly, and obtain a metal conductive material slurry.
[0075] Compared with the prior art, the present invention has the following advantages:
[0076] (1) The ceramic electronic components prepared by the present invention can be used in a liquid nitrogen cooling environment (77K to 223K). The superconductor powder helps the conductive path and the resistance value is significantly reduced to a minimum of 1×10 -4 Ω·cm, which greatly reduces the energy consumption of the components; (2) The metal composite conductive paste prepared by the present invention can be used for the inner electrodes and terminal electrodes of passive components such as chip varistors, thermistors, multilayer ceramic capacitors, multilayer inductors, and chip resistors. As the operating temperature of the superconducting oxide gradually increases, the original performance of the passive component can still be maintained when used at an absolute temperature of 200K. In addition, the superconducting oxide provides an impedance-free circuit path, reducing the energy loss and failure rate of the operating components, thereby greatly improving the reliability of passive component products in harsh low-temperature environments; (3) The advantage of the present invention is that it improves the reliability of passive component products in harsh low-temperature environments. By replacing glass powder with superconducting oxide and using the expansion coefficient of the superconducting oxide to adjust the expansion coefficient of the metal composite paste formed by the metal conductor to match the ceramic material, the impedance value of the metal composite paste can be reduced and the impedance value of the metal composite paste can be increased.
[0077] The above provision relates to its detailed technical content and inventive features. Those skilled in the art may make various modifications and substitutions according to the provision and suggestions of the present invention described without departing from the features of the present invention. However, although these modifications and substitutions are not fully provided in the above description, they are substantially covered in the following claims attached.
Claims
1. A superconductor-metal conductive material, characterized in that: It includes a metal powder, a superconductor powder and an organic carrier adhesive, wherein the metal powder accounts for 50-95wt% of the total weight of the metal powder, the superconductor powder and the organic carrier adhesive, the superconductor powder accounts for 4-40wt% of the total weight, and the organic carrier adhesive accounts for 1-10wt% of the total weight, wherein the superconductor powder includes one or more mixtures of La2-x-ySrxBayCuO4, La2-x-yBixSryCuO4, La2-xy-zBixSryCaZCuO4, La2-xy-zHgxBayCazCuO4, La2-x-ySrxTlyBazCuO6, La2-xyz-wSrxTlyBazCawCu2O8, HgBa2Ca2Cu3O8, wherein x, y, z and w are all between 0.1 and 0.
9.
2. The superconductor-metal conductive material according to claim 1, characterized in that: The average particle size of the superconductor powder is 30 nm to 300 nm.
3. The superconductor-metal conductive material according to claim 1, characterized in that: The metal powder includes one or more mixtures of Au, Ag, Cu, Sn, Ag / Pd, Pd, Al, Nb, Ti and Ni.
4. The superconductor-metal conductive material according to claim 1, characterized in that: The average particle size of the metal powder is 30 nm to 2 μm.
5. The superconductor-metal conductive material according to claim 1, characterized in that: The particle size of the metal powder is less than 100 nanometers, accounting for 10-20% of all metal powder particles, and the particle size of the metal powder is between 100 nm and 2 μm, accounting for 80-90% of all metal powder particles.
6. The superconductor-metal conductive material according to claim 1, characterized in that: The organic carrier binder includes one or more mixtures of polyvinyl butyral, ethyl cellulose, polyvinyl acetate, polyethylene oxide, carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, and polymethyl methacrylate.
7. The superconductor-metal conductive material according to claim 1, characterized in that: The superconductor-metal conductive material also includes an organic solvent, and the organic solvent is a mixture of one or more of toluene, alcohol, butyl acetate, ethylene glycol monobutyl ether, and diethylene glycol.
8. The superconductor-metal conductive material according to claim 1, characterized in that: The invention also comprises a dispersant, which comprises a mixture of one or more of carboxylic acids, long-chain alkyl amino acids, polyacrylic acids and polymethyl methacrylates.
9. An electronic component, characterized in that: include: A plurality of stacked composite layers, wherein each composite layer comprises a ceramic layer and a conductive layer made of a superconductor-metal conductive material coated on the ceramic layer, wherein the superconductor-metal conductive material comprises a metal powder, a superconductor powder and an organic carrier binder, wherein the metal powder accounts for 50-95wt% of the total weight of the metal powder, the superconductor powder and the organic carrier binder, the superconductor powder accounts for 4-40wt% of the total weight, and the organic carrier binder accounts for 1-10wt% of the total weight. t%, wherein the superconductor powder includes one or more mixtures of La2-x-ySrxBayCuO4, La2-x-yBixSryCuO4, La2-xy-zBixSryCaZCuO4, La2-xy-zHgxBayCazCuO4, La2-x-ySrxTlyBazCuO6, La2-xyz-wSrxTlyBazCawCu2O8, and HgBa2Ca2Cu3O8, wherein x, y, z and w are all between 0.1 and 0.
9.
10. The electronic component according to claim 9, characterized in that The average particle size of the superconductor powder is 30 nm to 300 nm.
11. The electronic component according to claim 9, characterized in that: The metal powder includes one or more mixtures of Au, Ag, Cu, Sn, Ag / Pd, Pd, Al, Nb, Ti and Ni.
12. The electronic component according to claim 9, characterized in that: The average particle size of the metal powder is 30 nm to 2 μm.
13. The electronic component according to claim 9, characterized in that The particle size of the metal powder is less than 100 nanometers, accounting for 10-20% of all metal powder particles, and the particle size of the metal powder is between 100 nm and 2 μm, accounting for 80-90% of all metal powder particles.
14. The electronic component according to claim 9, characterized in that The electronic component is a resistor.
15. The electronic component according to claim 9, characterized in that The electronic component is a varistor.
16. A method of forming an electronic component, characterized in that: include: coating a superconductor-metal conductive material on a ceramic layer to form a composite layer; The plurality of composite layers are stacked together, and the plurality of composite layers stacked together are sintered at a temperature above 800° C., wherein the superconductor-metal conductive material comprises a metal powder, a superconductor powder and an organic carrier binder, wherein the metal powder accounts for 50 to 95 wt % of the total weight of the metal powder, the superconductor powder and the organic carrier binder, the superconductor powder accounts for 4 to 40 wt % of the total weight, the organic carrier binder accounts for 1 to 10 wt % of the total weight, and the superconductor powder accounts for 1 to 10 wt % of the total weight. The conductor powder includes one or more mixtures of La2-x-ySrxBayCuO4, La2-x-yBixSryCuO4, La2-xy-zBixSryCaZCuO4, La2-xy-zHgxBayCazCuO4, La2-x-ySrxTlyBazCuO6, La2-xyz-wSrxTlyBazCawCu2O8, and HgBa2Ca2Cu3O8, wherein x, y, z and w are all between 0.1 and 0.
9.
17. The method according to claim 16, characterized in that The superconductor-metal conductive material is formed by the following steps: mixing 50-95 weight percent of metal powder with 4-40 weight percent of superconductor powder; adding 1-10 weight percent of organic carrier binder to the mixed powder; and adding the mixture into a solvent containing a dispersant to form the superconductor-metal conductive material.